Personal financial behavior among students: the case of UiTM Melaka / Zarinah Abu Yazid, Shahreena Daud and Nur Asyira Naziron - Abu Yazid, Zarinah; Daud, Shahreena; Naziron, Nur Asyira (Research Management Institute (RMI), 2012)
Financial management is very important to secure a good quality of life. People must plan for long-term investments for their retirement and children's education. They must decide on short-term savings and borrowing for a vacation, a down payment for a house and a car loan. Therefore, to make a good financial decision, we must have a proper financial planning and basically we need to start at a young age. Due to this, a study on personal financial behavior among students at Universiti Teknologi MARA Melaka was undertaken. The purpose of this paper is to highlight the impact of two independent variables (financial knowledge and financial attitude) on the dependent variable, personal financial behavior. Questionnaires were used to collect data and 143 students were involved as respondents. The collected data was then will be analyzed by using SPSS 20. Findings revealed that financial knowledge and financial attitude are significant predictors of students' personal financial behavior and it was concluded that financial knowledge has the most impact on the students' personal financial behavior. Recommendations for future research have also been put forth in this paper.